The Effects of Inventory Management Capability on Performance of the Firm- Business Strategies as a Mediating Role - Khan, Md. Sazzadur Rahman (Asian Finance & Banking Review, 2020)
The research aim is to evaluate the mediating aspects of business strategies e.g. differentiation and cost leadership strategy in affecting the aspects of inventory capability e.g. cost-related factors of inventory and techniques of inventory and firm performance e.g. return on asset (ROA) and improve productivity (IMP) of the Bangladeshi garment industry. A survey was utilized to collect information and the questionnaire was dispersed among 385 senior managers in the readymade garment industry of Bangladesh. For the data analysis, AMOS version 24 and SPSS version 23 were used. The findings of the analyzed data revealed that strategies of the business mediate the consequence of inventory materials capability and performance of the firm. The (SEM) results identify that the study model has an appropriate observation fits.